Measurement of the Vertical Distribution of Reflected Solar Radiation* - Tetsu Aoki; Akio Mizutani (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
The purpose of this study was to develop a devicefor measuring the vertical distribution of the reflected radiation to the inside of a room from terrace to building.The proposed device is attached to aluminum plates that are painted matte black at intervals of 20 cm on polystyrene insulation. The surface temperature of the aluminum plate, called the SAT (sol-air temperature), is used as an indicator of the quantity of solar radiation. In order to compare terrace materials, two of the measuring devices were located facing south.Concrete tile, artificial turf, and wood chips were selected as materials to be comparedfor the surface of the terrace and were laid in front of the measuring devices. The results indicate that the SAT reflected onto a vertical plane was higher closer to the ground for all materials. Hourly fluctuations of the vertical distribution of the reflected solar radiation differed, depending on the terrace surface material. When concrete tiles of different thicknesses were compared, the temporal heating patterns varied due to differences in heat capacity. These results lead us to the conclusion that using the developed measuringdevice enables grasping the effect of vertical distribution of reflected solar radiation from a terrace.